2018
DOI: 10.15201/hungeobull.67.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Nomen est omen – Tourist image of the Balkans

Abstract: The regime change, the South Slavic civil war, global recession and their political, economic and social consequences had a significant impact on the tourism market of Southeast Europe and the Balkan region. Many potential visitors to the region were affected by their negative associations with past events, even those that happened many years ago. The image of the Balkan region has become at times almost synonymous with conflict, turmoil and unrest. However, these perceptions may be changing and are therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Not only is nationalism potentially damaging for individual countries, but for the entire region as a whole. As Smith et al (2018) found in their research on tourism image in the Balkans on user-generated content websites like TripAdvisor, that opinions about tourist related services that use the word 'Balkans' in their reviews can shape the region's tourism-related image regardless of which country they are in. With this in mind and the rapid rate that global tourism is growing, it seems that the industry will not wait for the social and political tensions in the Balkans to resolve themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is nationalism potentially damaging for individual countries, but for the entire region as a whole. As Smith et al (2018) found in their research on tourism image in the Balkans on user-generated content websites like TripAdvisor, that opinions about tourist related services that use the word 'Balkans' in their reviews can shape the region's tourism-related image regardless of which country they are in. With this in mind and the rapid rate that global tourism is growing, it seems that the industry will not wait for the social and political tensions in the Balkans to resolve themselves.…”
Section: Discussionmentioning
confidence: 99%
“…We explored less immaterial local products just as legends and myths (Smith et al 2018). For instance, a myth came from the Eszterházy castle in Fertőd where a ghost room can be found in the desolate part of the building.…”
Section: Local Productsmentioning
confidence: 99%
“…In the names of tourist destinations, attractive-sounding geographical elements are used in many cases, which also refer to the characteristics and specific features of their tourism offer (Kavaratzis, M. and Ashworth, G. 2005;Smith, M. et al 2018). As its name, which turned into one with leisure and tourism, also suggests, the Danube Bend is characterized by the beautiful valley of the Danube, which forms a sharp curve as breaks through the Visegrad Strait (Photo 1).…”
Section: Study Areasmentioning
confidence: 99%